Direct estimation of the P-delta effect through the stability-coefficient-response-spectra by introducing the first-storey-single-degree-of-freedom system - Mousavi, Seyed Mohammad Fard; Sensoy, Serhan (Springer, 2019)
Present study introduces two concepts for direct estimation of P-delta effect in both, strength based, and displacement based design methods. Although various previously conducted studies focused on inclusion of P-delta effect into the aforementioned design methods, development of reliable procedures is still attractive. The major argument of present study is that: treatment of P-delta effect can be enhanced by using an alternative response/design spectrum. To this end, and based on period-dependence feature of stability coefficient (SC), the stability coefficient response spectra (SCRS) is introduced. The SCRS, plots spectral acceleration versus SC, instead of period, for a pendulum with known height. To facilitate implementation of SCRS on multi-degree-of-freedom systems, and by considering some special features of the first-storey, the concept of first-storey-single-degree-of-freedom (FSSDOF) system is introduced. The FSSDOF system permits setting the minimum necessary lateral stiffness, conforming to a pre-selected SC limit, and a given ductility level, at very early stages of design process. Moreover, it is shown that implementation of SCRS and FSSDOF system can be extended to account for drift limits. This is done by introducing a modified version of the yield-point-spectra method in which period-dependence feature of SC is recognized. Several numerical examples are included as part of the presentation.
Keywords: Stability-coefficient response spectra; First-storey single-degree-of-freedom-system; P-delta effect; Pendulum-based spectra; Inverted-pendulum